Evidências da associação entre testosteronas e doença periodontal no sexo masculino - Steffens, João Paulo [UNESP] (2013)
The hypothesis of this work is that sex hormones participate in the etiopathogenesis of periodontal disease (PD). Different levels of scientific evidence tested that hypothesis, evaluating: i. The association between sex hormones and PD in men; ii. The influence of sub- and supraphysiologic testosterone (T) levels on PD in rats; iii. If that mechanism of action involves osteoblast and osteoclast responses in vitro. Data from NHANES III related to diagnosis of PD and hormones measurement in 30+- year-old men were assessed to correlate those two variables. In rats, subphysiologic levels were obtained by orchiectomy and supraphysiolgic levels by T treatment. Half of the animals in each group received PD using a ligature model. In vitro, RAW264.7 cells were differentiated into osteoclastos in the presence of T (1nM-1μM) and identified by TRAP-staining. Murine osteoblast primary culture was used to evaluate the expression of osteocalcin, RANKL and OPG in the presence of T. In men, high levels of bioavailable T and low estradiol:T ratio significantly correlated with PD. In older men, low levels of AAG, a metabolite of dihydrotestosterone, also presented a significant correlation. In rats, low and high T levels significantly increased bone loss and modulated the expression of inflammatory cytokines. In vitro, physiologic T doses prevented osteoclastogenesis and decreased the expression of osteocalcin, RANKL and RANKL:OPG ratio produced by osteoblasts. We concluded that T modulates host response to PD in males, regulating osteoclast differentiation direct and indirectly (through osteoblasts).